2006
DOI: 10.1111/j.1460-9568.2006.05149.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of Alzheimer's model mice with Aβ derivative in alum adjuvant reduces Aβ burden without microhemorrhages

Abstract: Immunotherapy holds great promise for Alzheimer's disease (AD) and other conformational disorders but certain adverse reactions need to be overcome. The meningoencephalitis observed in the first AD vaccination trial was likely related to excessive cell-mediated immunity caused by the immunogen, amyloid-β (Aβ) 1-42, and the adjuvant, QS-21. To avoid this toxicity, we have been using Aβ derivatives in alum adjuvant that promotes humoral immunity. Other potential side effects of immunotherapy are increased vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
94
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 48 publications
(91 reference statements)
11
94
2
Order By: Relevance
“…In the current study we used K6-A␤1-30 chelated to gadolinium via incorporation of DPTA at the amino terminus. In our previously published studies we used K6-A␤1-30 as a vaccine therapy in AD model mice and have shown that this peptide is both non-toxic and non-fibrillogenic (Sigurdsson et al, 2001;Asuni et al, 2006). In the current study we have also demonstrated that this A␤ homologous peptide is nontoxic when labeled with chelated Gd (Fig.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the current study we used K6-A␤1-30 chelated to gadolinium via incorporation of DPTA at the amino terminus. In our previously published studies we used K6-A␤1-30 as a vaccine therapy in AD model mice and have shown that this peptide is both non-toxic and non-fibrillogenic (Sigurdsson et al, 2001;Asuni et al, 2006). In the current study we have also demonstrated that this A␤ homologous peptide is nontoxic when labeled with chelated Gd (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…We designed these homologous peptides so that they still have a high binding affinity to wild-type A␤ peptides and also have a similar BBB permeability. In prior studies we have shown that these A␤ homologous peptides do not self-assemble or promote the fibrillization of endogenous A␤ peptides (Asuni et al, 2006;Sigurdsson et al, 2001Sigurdsson et al, , 2004a). In the current study we used K6-A␤1-30 chelated to gadolinium via incorporation of DPTA at the amino terminus.…”
Section: Discussionmentioning
confidence: 93%
“…The A␤ species mass (monomers, oligomers, and proteolytic fragments) was computed by comparison with reference proteins (1.4 -27 kDa and 14 -97 kDa ladders; Bio-Rad). Oligomer disappearance was monitored by densitometry of the SDS-stable trimer, tetramer, and high mass oligomer bands (45 kDa band, 64 -84 kDa smear) following staining of gel blots with a mixture of mouse anti-A␤ monoclonal IgG 6E10, IgG 4G8 (both from Covance, Princeton, NJ), and IgG 6D4 (MyBioSource, San Diego, CA) (directed to A␤ (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), A␤ (17)(18)(19)(20)(21)(22)(23)(24), and the A␤ C terminus, respectively). Freshly dissolved A␤42 without prior oligomerization was mixed immediately with the nIgVs (3 g/ml) to test the nIgV effect on oligomer accumulation over 24 h of incubation at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The analyzed neocortical area was dorsomedial from the cingulate cortex and extended ventrolaterally to the rhinal fissure within the right hemisphere (measured field 700 ϫ 700 m). Left brain hemispheres after removing the olfactory bulb were homogenized as described (24). The hemispheres were weighed and homogenized (10%, w/v) in 20 mM Tris base, 250 mM sucrose, 1 mM EDTA, 1 mM EGTA, 100 mM phenylmethylsulfonyl fluoride, 5 g/ml pepstatin A, and a 25-fold dilution of cOmplete protease inhibitor mixture as recommended by the supplier (Roche Applied Science).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation